Damage to the Cardiovascular System in Patients with SARS-CoV-2 Coronavirus Infection. Part 2: Correction of Myocardial Systolic Dysfunction - V. I. Podzolkov; A. I. Tarzimanova; A. E. Bragina; I. I. Shvedov; E. E. Bykova; A. A. Ivannikov; L. V. Vasilyeva (Рациональная фармакотерапия в кардиологии)
Aim. To study changes in myocardial contractile function when prescribing mineralocorticoid receptor antagonists of spironolactone in patients after coronavirus infection SARS-CoV-2 with symptoms of chronic heart failure (CHF).Materials and methods. The study included 90 hospitalized patients with a diagnosis of SARS-CoV-2 coronavirus infection. The inclusion criteria were: age from 18 to 85 years; the presence of CHF with a preserved or mildly reduced left ventricular ejection fraction (LVEF). The patients were randomized into two groups: group I (n=60) included patients who, for 6 months after discharge from the hospital, in addition to standard drug therapy for CHF, took spironolactone at a dose of 25 mg per day; group II (comparison group; n=30) included patients who received standard drug therapy without additional prescription of spironolactone. The study groups were comparable in age, gender, prevalence of hypertension, coronary heart disease, diabetes mellitus, obesity and severity of CHF; the drug therapy given to the patients had no significant differences. Assessment of LV systolic function, exercise tolerance (six-minute walk test, TSW), quality of life (questionnaire EQ-5D-5L) were performed.Results. When repeated echocardiography was performed after 6 months of treatment, there was a significant improvement in LV systolic function in group I patients. In group I, after 6 months of treatment, there was a significant decrease in the proportion of patients with moderately reduced LVEF (from 30 [50%] to 12 [20%]; p<0.001), and a significant increase in the number of patients with preserved LVEF (from 30 [50%] to 48 [80%], p=0.002). In group II, the number of patients with moderately reduced LVEF did not significantly change. After 6 months of treatment, all patients showed an increase in exercise tolerance. During the test with a six-minute walk, group I patients showed an increase in the index from 316.8±63.5 to 432.9±41.3 meters; group II patients from 337.6±42.7 to 407.6±38.9 meters. The values of the six-minute walking test after 6 months of treatment were significantly higher in group I patients when compared with group II patients. When assessing the quality of life using the EQ-5D-5L questionnaire, it was found that at the time of inclusion of patients in the study, all patients noted the presence of any health problems in one or more components. The average indicator of health status, measured by a 100-point visual analog scale, after 6 months was 71.8±9.2 in patients of group I and was significantly higher than the same indicator in group II – 63.7±9.1. There were no adverse events in the study groups during the entire observation period.Conclusion. A significantly more pronounced improvement in systolic and diastolic left ventricle function, as well as quality of life, was found in the group of CHF patients with preserved or moderately reduced LVEF, who received spironolactone for 6 months after the SARS-CoV-2 infection in addition to standard therapy, compared with patients without aldosterone antagonists.